Análisis de las normas contables al control de los activos bajo normas tributarias y aplicación de la NIC 16. - Mosquera Aguilar, Christian Alberto (My University, 2021)
Within the business field, entities have properties, plant and equipment to operate and which in turn help to generate income thanks to the production and manufacture of products or services. These in turn form the assets of Property, Plant and Equipment that are contained under International Accounting Standard 16, where the scope and objective are explained, so that at the end of a period the financial activities of the company are clear business; for this reason, the purpose of this work is to study IAS 16, to ensure adequate control of the elements of property, plant and equipment without affecting the tax obligation, in which a theoretical study will be applied, based on theoretical foundations, Regulations and fundamental concepts that facilitate the understanding and subsequent application of the regulations. It should be noted that within this work a descriptive and bibliographic methodology is used. Finally, the analysis of this regulation will allow us to answer the question and thus help the company RENO'S, which markets venison fillets, to properly apply the accounting standards to the control of property, plant and equipment assets under the control of tax regulations and as the companies are based on the International Financial Reporting Standards (IFRS).
Dentro del campo empresarial, las entidades cuentan con propiedades, planta y equipos para poder operar y que a su vez ayudan a generar ingresos gracias a la producción y fabricación de productos o servicios. Estos forman a su vez de los activos de Propiedad, Planta y Equipo que está contenido bajo la Norma Internacional de Contabilidad 16, en donde se explica el alcance y objetivo, para que al final de un período se tenga en claro las actividades financieras de la empresa; por tal razón, el presente trabajo tiene como finalidad el estudio de la NIC 16, para asegurar un adecuado control de los elementos de propiedades, planta y equipos sin afectar la obligación tributaria, en el que se aplicará un estudio teórico, basado en fundamentos teóricos, normativas y conceptos fundamentales que faciliten el entendimiento y posterior aplicación de la normativa. Cabe recalcar que dentro de este trabajo se hace uso de una metodología descriptiva y bibliográfica. Finalmente el análisis de esta normativa permitirá dar respuesta a la interrogante y así ayudar a la empresa RENO´S que comercializa filetes de carne de venado, a aplicar adecuadamente las normas contables al control de los activos de propiedades, planta y equipos bajo el control de normas tributarias y según se basan las empresas en las Normas Internacionales de Información Financiera (NIIF).
Keywords: CONTABILIDAD; GESTIÓN CONTABLE; AUDITORÍA